Espace et variation linguistique : description et modélisation. Les bases de données THESOC et ALCANOM - Jean-Philippe Dalbera (La Bretagne Linguistique, 1998)
This article presents two tools currently under development: the Occitan Thesaurus (THESOC) and ALCANOM (Atlas linguistique des Côtes de l'Arc Nord-Occidental de la Méditerranée). THESOC aims to bring together Occitan lexical data scattered across several atlases and monographs. ALCANOM covers an area stretching from the south of Catalonia to Tuscany and deals more specifically with ichthyonymy and fishing.